PEG-b-PPA/DNA micelles improve transgene expression in rat liver through intrabiliary infusion - Jiang, Xuan (2007)
We have developed a new block copolymer gene carrier that comprises of a polyethylene glycol segment and a degradable cationic polyphosphoramidate (PPA) segment. This PEG-b-PPA copolymer carrier formed micelles upon condensation with plasmid DNA in aqueous solution. PEG-b-PPA/DNA micelles exhibited uniform and reduced particle size ranging from 80 to 100 nm and lowered surface charge, compared with complexes of DNA with the corresponding cationic PPA carrier. PEG-b-PPA/DNA micelles maintained similar transfection efficiency as PPA/DNA complexes, which was comparable to that of PEI/DNA complexes in HepG2 cells, but yielded about 16-fold lower transgene expression in primary rat hepatocytes than PPA/DNA complexes. Following bile duct infusion in Wistar rats, PEG-b-PPA/DNA micelles mediated 4-fold higher and more uniform gene expression in the liver than PPA/DNA complexes. Liver function tests and histopathological examination indicated that PEG-b-PPA/DNA micelles showed low toxicity and good biocompatibility in the liver. This study demonstrated the potential of PEG-b-PPA/DNA micelles as an efficient carrier for liver-targeted gene delivery.